PENEGAKAN HUKUM PIDANA ATAS PEREDARAN JAMU YANG MENGANDUNG BAHAN KIMIA OBAT BERBAHAYA DI KOTA PEKANBARU - Robin Aritonang; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
BPOM Pekanbaru has issued a circular regarding the list of herbscontaining dangerous medicinal chemicals to distributors and shops so as not tosell any more herbs identified by BPOM Pekanbaru that contain hazardousmedicinal chemicals. The results of a raid conducted by BPOM Pekanbaru founda drug store selling herbal medicine containing dangerous medicinal chemicals,such as the brand Akar Dewa herbal medicine produced by UD. Image of Nature,East Java. This herbal root god is circulating freely in Pekanbaru. This herbcontains the chemical piroxicam. The use of piroxicam in high doses can causekidney damage.The type of legal research is sociological juridical, which in this research,is carried out by going directly to the field to collect primary data, and usingdescriptive methods. Meanwhile, if viewed from the nature of this research isdescriptive.The results of this study are the enforcement of criminal law on thecirculation of herbal medicine containing dangerous medicinal chemicals in thecity of Pekanbaru by conducting inspections, investigations and the application ofsanctions but has not been able to run optimally. The obstacles found in theenforcement of criminal law on the circulation of herbal medicine containinghazardous medicinal chemicals in the city of Pekanbaru are inadequatesupervision, limited authority of BBMP, lack of participation and support fromthe community, low public understanding of the law, and lack of intensity ofsocialization activities. Efforts were made to overcome the obstacles found incriminal law enforcement on the circulation of herbal medicine containinghazardous medicinal chemicals in the city of Pekanbaru, namely law enforcementoperations, socialization and optimizing cooperation with related parties and thecommunity.Keywords: Criminal Law Enforcement, Herbal Medicine, Hazardous DrugChemicals.